Authority in rebel groups: identity, recognition and the struggle over legitimacy. Issue 4 (2nd October 2017) - Brenner, David
ABSTRACT: This article asks how rebel leaders capture and lose legitimacy within their own movement. Analysing these complex and often uneasy relations between elites and grassroots of insurgency is important for understanding the success or failure of peace processes. This is because internal contestation over authority between rival rebel leaders can drive a movement's external strategy. Based on ethnographic research on the Karen and Kachin rebellions in Myanmar and insights from Political Sociology, the article suggests that leadership authority is linked to social identification and the claim to recognition among insurgent grassroots. If rebel leaders manage to satisfy their grassroots' claim to recognition, their insurgent orders are stable. Failing this, their authority erodes and is likely to be challenged. These findings contribute to understanding insurgency and peace negotiations in Myanmar and civil wars more generally by showing how struggles over legitimacy within rebel groups drive wider dynamics of war and peace.